2020
DOI: 10.1111/jcmm.16182
|View full text |Cite
|
Sign up to set email alerts
|

The protective effect of isosteviol sodium on cardiac function and myocardial remodelling in transverse aortic constriction rat

Abstract: Cardiac hypertrophy is a compensatory response to pressure overload and a key risk factor for heart failure. 1-3 The cardiac function generally becomes deteriorative during the transition from compensated to decompensated cardiac hypertrophy. 4,5 The cardiac remodelling characterized by cardiac fibrosis that significantly reduces cardiac function and electrophysiological remodelling also occurs during the cardiac hypertrophy. 6-9 The process of cardiac hypertrophy is also accompanied by abnormal electrophysiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Despite this, there are not many studies on the potentiality of STV-Na therapeutic effects for ALI. [16][17][18] Prior research have confirmed that STV-Na can reduce the activity of NF-κB/p65. 18 We therefore utilized a LPS-induced acute lung injury model and explored whether STV-Na has a potential therapeutic impact on lung injury and the intrinsic mechanisms associated with it.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Despite this, there are not many studies on the potentiality of STV-Na therapeutic effects for ALI. [16][17][18] Prior research have confirmed that STV-Na can reduce the activity of NF-κB/p65. 18 We therefore utilized a LPS-induced acute lung injury model and explored whether STV-Na has a potential therapeutic impact on lung injury and the intrinsic mechanisms associated with it.…”
Section: Introductionmentioning
confidence: 97%
“…it was found that STV‐Na inhibited macrophage polarization to reduce inflammatory cytokine production and attenuated LPS‐induced multiorgan damage. Despite this, there are not many studies on the potentiality of STV‐Na therapeutic effects for ALI 16–18 . Prior research have confirmed that STV‐Na can reduce the activity of NF‐ κB/p65 18 .…”
Section: Introductionmentioning
confidence: 99%
“…9 Numerous experimental studies have shown that traditional Chinese herbal medicines are more effective in the treatment of cardiovascular diseases, including ischaemic heart disease, and that the natural substances in herbal medicines are not only green and safe, with few side effects, but also have strong anti-oxidant and anti-apoptotic properties. [10][11][12] Nanotechnology has been a hot topic of research in recent years and has had a huge impact on the innovation and development of medicine, including nano-pharmaceuticals, nano-biomaterials and nano-biosensors. [13][14][15] Meanwhile, nanotechnology has great potential for the treatment and detection of cardiovascular diseases.…”
Section: Introductionmentioning
confidence: 99%